2022
DOI: 10.1155/2022/4185972
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages with Different Polarization Phenotypes Influence Cementoblast Mineralization through Exosomes

Abstract: Root resorption is a common dental challenge that can lead to tooth loosening or even tooth loss. Among the cells involved in root resorption, cementoblasts are responsible for laying down the cementum, while macrophages with different phenotypes have also been shown to have bidirectional effects on root resorption. However, the relationship between macrophages and cementoblasts remains largely unknown. In this study, we examined the effect of macrophages with different polarization phenotypes on the mineraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Only 2 in vivo studies have investigated the role of exosomes in tooth movement and tooth resorption caused by tooth movement (Table 10). In the study by Zhao et al., 47 the mouse RAW264.7 monocyte cell line was investigated, including their M0, M1 and M2 phenotypes. By isolating M0/M1/M2 macrophage exosomes and analyzing their impact on cementoblast mineralization, it was found that the effects of macrophages on cementoblast mineralization were at least partially exerted by exosomes 47 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 2 in vivo studies have investigated the role of exosomes in tooth movement and tooth resorption caused by tooth movement (Table 10). In the study by Zhao et al., 47 the mouse RAW264.7 monocyte cell line was investigated, including their M0, M1 and M2 phenotypes. By isolating M0/M1/M2 macrophage exosomes and analyzing their impact on cementoblast mineralization, it was found that the effects of macrophages on cementoblast mineralization were at least partially exerted by exosomes 47 .…”
Section: Resultsmentioning
confidence: 99%
“…By isolating M0/M1/M2 macrophage exosomes and analyzing their impact on cementoblast mineralization, it was found that the effects of macrophages on cementoblast mineralization were at least partially exerted by exosomes. 47 A study by Liu et al 85 found that encapsulating simvastatin into exosomes derived from PDLSCs improved simvastatin solubility and enhanced the inhibitory effect of relapse in a rat model of orthodontic tooth movement (OTM). Notably, local injection of PDLC-Exos alone could also block relapse after OTM.…”
Section: Orthodontic Tooth Movementmentioning
confidence: 99%
“…Additionally, they used the orthodontic tooth movement strategy combined with gingival crevicular injection of LPS to construct the cementum absorption model, followed by the injection of different kinds of M-EVs. Their results indicated that M2-EVs could also significantly promote cementoblast mineralization in vivo [ 106 ]. Our unpublished study demonstrated that Ckip-1 (casein kinase 2-interacting protein 1)-silenced macrophage-derived CEVs (sh-Ckip-1-EVs) possesses the characteristic of M2-EVs in facilitating cementoblast mineralization.…”
Section: Cevs and Periodontal Regenerationmentioning
confidence: 99%
“…A recently published paper showed that the effects of macrophages on cementoblast mineralization were mediated by exosomes. Compared with M0 (unpolarized macrophages), M1-polarized macrophages attenuated cementoblast mineralization, while M2-polarized macrophages enhanced cementoblast mineralization ( Zhao et al, 2022 ). However, there are few articles about EVs promoting cementum regeneration.…”
Section: The Use Of Evs In Oral and Maxillofacial Tissue Repair And R...mentioning
confidence: 99%